2016
DOI: 10.1080/10790268.2016.1168587
|View full text |Cite
|
Sign up to set email alerts
|

Central fatigue in multiple sclerosis: a review of the literature

Abstract: Future research on MS-related fatigue may consider a longitudinal design with a carefully selected self-report instrument to advance understanding of the underlying pathological mechanisms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
42
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(46 citation statements)
references
References 63 publications
3
42
0
1
Order By: Relevance
“…The researchers believes that fatigue severity in MS was increases in those who were older and had a longer time, since symptom onset occur and could be effect on; cognitive, motor functioning, social activity or relationships, therefore early symptoms management in MS is a key strategy to effective self management. This finding in line with [6,35] who noted that fatigue in MS after (15)(16)(17)(18)(19)(20) years of symptom onset, can lead to progressive course or clinical deterioration of MS. [52] added that fatigue in MS patients is associated with reduced employment and lower quality of life over time. In addition [6] explained that early management of fatigue in MS can help in starting a suitable treatment and prevent complication.…”
Section: Discussionsupporting
confidence: 85%
“…The researchers believes that fatigue severity in MS was increases in those who were older and had a longer time, since symptom onset occur and could be effect on; cognitive, motor functioning, social activity or relationships, therefore early symptoms management in MS is a key strategy to effective self management. This finding in line with [6,35] who noted that fatigue in MS after (15)(16)(17)(18)(19)(20) years of symptom onset, can lead to progressive course or clinical deterioration of MS. [52] added that fatigue in MS patients is associated with reduced employment and lower quality of life over time. In addition [6] explained that early management of fatigue in MS can help in starting a suitable treatment and prevent complication.…”
Section: Discussionsupporting
confidence: 85%
“…Fatigue was known as a debilitating symptom, which was frequently reported among MS patients 32, 33. Little is understood about the mechanisms and determinants of fatigue 34. Axonal damage as measured by N‐acetylaspartate‐creatinine ratio on proton magnetic resonance spectroscopy scanning have been associated with fatigue in MS patients 35.…”
Section: Discussionmentioning
confidence: 99%
“…32,33 Little is understood about the mechanisms and determinants of fatigue. 34 Axonal damage as measured by N-acetylaspartate-creatinine ratio on proton magnetic resonance spectroscopy scanning have been associated with fatigue in MS patients. 35 Our results supported these findings, and may provide serum NfL as a potential biomarker and predictor of fatigue, which may be utilized in clinical monitoring or for clinical trials.…”
Section: Discussionmentioning
confidence: 99%
“…An accelerating rotarod test revealed that UNC5B cKOs were able to learn the task to a level equal to controls, but intriguingly, aged animals exhibited a deficit in the rate of acquisition to learn the motor skill. The delay in motor learning may result from increased fatigue, as myelin disruption can increase fatigue (Simpson et al, 2016), and fatigue is a prominent symptom in demyelinating diseases like multiple sclerosis (Freal et al, 1984;Krupp et al, 1988;Newland et al, 2016); however, UNC5B deletion may also disrupt some aspect of myelin plasticity, which is increasingly understood to play roles in learning, including motor learning (Chorghay et al, 2018;de Faria et al, 2018).…”
Section: Discussionmentioning
confidence: 99%